Stories and poems for extremely intelligent children of all ages - Bloom, Harold (New York : Scribner, 2001)
A collection of stories and poems, arranged in four sections corresponding to the four seasons.
Fourth year high school and above
Keywords: Children's literature; Literature -- Collections